ANALISIS PENGARUH RISIKO KREDIT, RISIKO PASAR, EFISIENSI OPERASI, MODAL, DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN PERBANKAN (Studi Kasus pada Bank Usaha Milik Negara yang Terdaftar di BEI Periode 2009-2012) - Pauline Natalia (STIE Indonesia Banking School, 2015)
The objective of this research is to examine and analyze the impact of credit risk, market risk, operation efficiency, capital, and liquidity toward the financial performance of banks. This research used quantitative research design. The data used in this research are all state-owned banks listed in Bursa Efek Indonesia (BEI) from the year 2009-2012. The type of data is secondary data. Technical analysis used multiple linear regression. The result shows that market risk and operation efficiency have significant influence to financial performance of banks. Meanwhile, credit risk, capital, and liquidity do not have significant influence to financial performance of banks.